2021
DOI: 10.1158/2159-8290.cd-20-1508
|View full text |Cite
|
Sign up to set email alerts
|

Werner Helicase Is a Synthetic-Lethal Vulnerability in Mismatch Repair–Deficient Colorectal Cancer Refractory to Targeted Therapies, Chemotherapy, and Immunotherapy

Abstract: Targeted therapies, chemotherapy, and immunotherapy are used to treat patients with mismatch repair-deficient (dMMR)/microsatellite instability-high (MSI-H) colorectal cancer (CRC). The clinical effectiveness of targeted therapy and chemotherapy is limited by resistance and drug toxicities, and about half of immunotherapy patients are refractory to immune checkpoint inhibitors. Loss of Werner syndrome ATP-dependent helicase (WRN) is a synthetic-lethality in dMMR/MSI-H cells. To inform the development of WRN as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 62 publications
0
62
0
Order By: Relevance
“…Chemotherapy resistance has been recognized as a major problem in cancer therapy, reducing the cytotoxic activity of anticancer agents. In addition to drug resistance after repeated use, the obvious toxic effects of chemotherapy drugs limit their clinical application [ 44 ]. Hence, the efficacy and tolerance of targeted drugs need to be simultaneously considered when hunting for targets after chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy resistance has been recognized as a major problem in cancer therapy, reducing the cytotoxic activity of anticancer agents. In addition to drug resistance after repeated use, the obvious toxic effects of chemotherapy drugs limit their clinical application [ 44 ]. Hence, the efficacy and tolerance of targeted drugs need to be simultaneously considered when hunting for targets after chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years the progress in cancer immunology has radically changed therapeutic strategies for the treatment of many types of solid tumors including colorectal cancer. For now, it is well-documented that drugs named immune checkpoint inhibitors are effective in a small subset of mismatch repair de cient (MMRd) malignancies [3,4,28]. Mismatch repair stable cancers represent the vast majority of CRCs and exhibit primary resistance to immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The international CRC subtyping consortium has de ned four molecular subtypes of CRC: consensus molecular subtypes (CMS)1 to CMS4, each of which has a characteristic molecular background characterized by a distinct gene expression, mutational status and in ammatory microenvironment [3]. However, this strati cation is not unambiguous, since also de ned subtypes often displaying intratumoral heterogeneity, whereby several subpopulations within one tumor show differences in in ammatory in ltrate, mutations and morphology [3,4]. These studies thus revealed that CRC is not one disease, but rather a collection of neoplastic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The same group recently identified several non-specific reversible and irreversible helicase inhibitors through HTS using a larger library of approximately 350,000 small molecules ( 222 ). Several studies identified WRN synthetic lethal vulnerability in cancers with microsatellite instability ( 218 , 223 , 224 ), suggesting specific WRN inhibitors hold great potential to target microsatellite instability tumors to enable a clear stratification path in the clinic.…”
Section: Inhibitors Targeting Ssa and Alt-nhej (Tmej) Pathwaysmentioning
confidence: 99%